Islamic banking vs. conventional banking: a comparative study on Exim Bank Ltd & Dutch Bangla Bank Ltd. - Koyel, Sanjida Sharmin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.